THE INFLUENCE OF THE QUALITY OF GOOD CORPORATE GOVERNANCE (GCG) IMPLEMENTATION ON FINANCIAL PERFORMANCE IN ISLAMIC COMMERCIAL BANKS IN INDONESIA - Siti Maesaroh; Sri Wahyuni Asnaini; Fatrilia Rasyi Radita (Universitas Insan Pembangunan Indonesia, 2022)
ABSTRACTCorporate governance arises from the business need for good governance, which upholds the principles of transparency, trustworthiness, responsibility and fairness. Good Corporate Governance is corporate governance which is assessed as one of the public's assessments in deciding to invest in a corporate institution. The indicator to assess the quality of the implementation of Good Corporate Governance is seen from the Self-Assessment of each company which is taken from 11 criteria that apply as a whole.The purpose of this study was to analyze the determinants the effect of the implementation of Good Corporate Governance (GCG) on financial performance as measured by Return on Assets (ROA) and Non-Performing Financing (NPF) at Islamic Commercial Banks in Indonesia. The population is all Islamic Commercial Banks that have implemented GCG in accordance with Bank Indonesia regulations. This research is associative to see the relationship between one variable and another. The data used is secondary data from annual reports and corporate governance reports issued by each Islamic Commercial Bank for the 2016-2020 periods. The sample collected is 8 Islamic commercial banks with a total of N = 40. The results show that the implementation of GCG based on the data collected has an average of 1:55 to 2:20 which is included in the